Evaluation of the clinical educational environment based on the DREEM model from the viewpoint of the OR students - Nasrin Galehdar; Maryam Habibi; Farzad Ebrahimzadeh; Behzad Moradi (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: The most important part of learning happens in the clinic. To determine the differences between the real educational environment and the desirable environment, the DREEM1 model is used. The present study was conducted to evaluate the clinical educational environment based on the DREEM model from the viewpoint of the OR2 students of the Lorestan University of Medical Sciences. MATERIALS AND METHODS: The present descriptive-analytical cross-sectional study evaluated the viewpoint of 118 students of operation room (OR) technology using the DREEM (Dundee Ready Educational Environment Measure) questionnaire in the hospitals affiliated with the Lorestan University of Medical Sciences during the second semester of 2020. The DREEM questionnaire has 50 statements and is divided into five sections, which are rated on a five-point Likert scale (0-4). The data were analyzed using frequency distribution tables, mean and standard deviation indices, Mann-Whitney and Kruskal-Wallis tests. Data analysis was conducted using IBM SPSS Statistics 22.0. IBM Corp.; 2013. and the level of significance was set at 0.05. RESULTS: The total perception of the students of the clinical educational environment was good and excellent in 73.8% of the cases and of the subscales was also good (50.8%-63.2%). There was a significant relation between the total score of students' perception of the clinical educational environment and age (Z = 5.618, P < 0.001), semester (χ2 = 43.929, df = 3, P < 0.001), internship hospital (χ2 = 12.948, df = 6, P = 0.044) and also the mean score of the subscales (P < 0.001). As the GPA3 and interest in the major increased, the mean score of total perception and its subscales also increased except for perception from the educators (P < 0.05). CONCLUSION: According to the results, the studied students had a positive perception of the clinical educational environment. It is recommended that the scientific foundation of the educators, the physical facilities of the operating rooms, and social communication should be strengthened to improve the care, treatment, and educational services. It will be useful to use the results to improve the accreditation level of medical centers.